2022
DOI: 10.1002/jbt.23025
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB‐upregulated miR‐155‐5p promotes hepatocyte mitochondrial dysfunction to accelerate the development of nonalcoholic fatty liver disease through downregulation of STC1

Abstract: Previous studies have highlighted the involvement of nuclear factor kappa B (NF‐κB) in the development of nonalcoholic fatty liver disease (NAFLD). The purpose of our investigation is to explore the interaction among NF‐κB, microRNA‐155‐5p (miR‐155‐5p), and Stanniocalcin 1 (STC1), and its effects on NAFLD by establishing a NAFLD model in Sprague Dawley rats. A highly‐expressed miR‐155‐5p and NF‐κB was revealed in the liver tissues of NAFLD rats, and a positive correlation was identified between miR‐155‐5p and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In the present study, we discovered that HTG refreshed the liver miRNA pro le in dyslipidemia rats, especially rno-miR-155-5p. MiR-155-5p was found to be highly-expressed in the liver tissues of NAFLD rats and promoted NAFLD progression [14] . On the other hand, miR-155-5p regulated cholesterol e ux and ameliorate atherosclerosis [15][16] Here, we elucidated that HTG administration disrupted miR-155-5p expression and lipid accumulation in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we discovered that HTG refreshed the liver miRNA pro le in dyslipidemia rats, especially rno-miR-155-5p. MiR-155-5p was found to be highly-expressed in the liver tissues of NAFLD rats and promoted NAFLD progression [14] . On the other hand, miR-155-5p regulated cholesterol e ux and ameliorate atherosclerosis [15][16] Here, we elucidated that HTG administration disrupted miR-155-5p expression and lipid accumulation in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that HTG restored the liver miRNA profile in dyslipidaemic rats, especially that of rno-miR-155-5p. MiR-155-5p was found to be highly expressed in the liver tissues of NAFLD rats and to promote NAFLD progression [18]. Moreover, miR-155-5p regulates cholesterol efflux and promotes atherosclerosis [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of LncARSR correlates with the activated state of PI3K/AKT/ mTOR pathway [99] miR-155 Upregulated These ncRNASs have an influence on the induction of inflammation via NF-κB pathway [100,101] Platr4 Upregulated [102] LncTNF Upregulated [103] miR-125 Upregulated…”
Section: Non-coding Rna Expression Primary Function Referencementioning
confidence: 99%
“…Studies have shown that activated NF-κB can induce or inhibit miRNA expression. Shen et al showed a correlation between increased miR-155 expression and active NF-κB levels in NAFLD-rat model, suggesting that NF-κB could induce miR-155 expression and enhance inflammation [100]. Furthermore, it has been reported that miR-155 hampers the expression of several transcripts that act as a TNF-α suppressor [101].…”
Section: Ncrna Inflammation and Fibrosismentioning
confidence: 99%